2019
DOI: 10.7759/cureus.5572
|View full text |Cite
|
Sign up to set email alerts
|

Local Wound Infiltration with Ropivacaine for Postoperative Pain Control in Caesarean Section

Abstract: BackgroundThe rate of the caesarean section has been on a progressive rise ever since its association with improved fetal prognosis was established. This study was conducted to assess the effect of local wound infiltration with ropivacaine on the postoperative analgesia requirement and pain scores in caesarean section patients.MethodsThis was a prospective single-blinded randomized control trial conducted at the Department of Obstetrics and Gynecology, KRL Hospital, Islamabad, Pakistan over a duration of six m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
2
11
0
Order By: Relevance
“…This result is in line with the study done by Nasir F et al [ 19 ] which found a significantly prolonged median time to request the first analgesia (4.49 ± 1.12) in WSI compared to the control group (2.36 ± 0.58). Another prospective cohort study conducted by H Million et al [ 15 ] also showed the extended median time to request the first analgesia in WSI 5.26 (9.03 ± 4.12) compared to the non-exposed group 3.46 (5.02 _2.46).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This result is in line with the study done by Nasir F et al [ 19 ] which found a significantly prolonged median time to request the first analgesia (4.49 ± 1.12) in WSI compared to the control group (2.36 ± 0.58). Another prospective cohort study conducted by H Million et al [ 15 ] also showed the extended median time to request the first analgesia in WSI 5.26 (9.03 ± 4.12) compared to the non-exposed group 3.46 (5.02 _2.46).…”
Section: Discussionsupporting
confidence: 92%
“…With regards to the severity of postoperative pain, our study demonstrated a lower NRS score at the 4th, and 6th hours postoperatively in the WSI group compared to the control group with P-values of <0.001 and 0.04 respectively. Similarly, studies reported a significant reduction of Verbal NRS or VAS pain score at 4th and 6th hr postoperative period respectively [ 15 , 19 ].…”
Section: Discussionmentioning
confidence: 93%
“…Three studies demonstrated that local anaesthetic wound infiltration reduced pain scores and the need for rescue analgesia during the first 24 h after caesarean section [71][72][73], while one study showed only limited benefits [74]. Apart from one study [72], basic analgesia with ibuprofen and paracetamol was provided.…”
Section: Local and Regional Analgesia Techniquesmentioning
confidence: 99%
“…7 Use of long acting local anesthetics to reduce pain and promote mobility. 109-112 Utilize surgical techniques to decrease or prevent Jackson Pratt drain use. 113,114 …”
Section: Eras Bl Protocolmentioning
confidence: 99%
“…125,126 PO food ad lib. Advance as tolerated Postoperative pain medications—opioid reduction protocol (limited narcotics with liposound, bupivacaine, benzodiazepines, and antiemetics, transition to OTCs 110-114,127 TED hose worn until POD 5. SCD use at home while not ambulating.…”
Section: Eras Bl Protocolmentioning
confidence: 99%